Comprehensive analysis indicated that NDE1 is a potential biomarker for pan‐cancer and promotes bladder cancer progression - Peihan Wang; Jinzhuo Ning; Wu Chen; Fan Zou; Weimin Yu; Ting Rao; Fan Cheng (Cancer Medicine, 2024)
Abstract Background The nuclear distribution E homologue 1 (NDE1) is a crucial dynein binding partner. The NDE1 protein has the potential to disrupt the normal functioning of centrosomes, leading to a compromised ability to generate spindles and ensure precise separation of chromosomes during cell division. The potential consequences of this phenomenon include genomic instability, malignant transformation and the proliferation of neoplastic growths. However, studies examining the connection between NDE1 and cancer is still very rare. Methods The expression level, prognostic impact, gene change, DNA methylation, protein interaction, mRNA m6A modification, ceRNA network, associated gene and function enrichment, and immune‐related effects of NDE1 in pan‐cancer were examined using a range of online analytic tools and the R software package. The CCK‐8 test, transwell assay, scratch assay and colony formation assay were used to confirm the effects of NDE1 on the proliferation, invasion and metastasis of bladder cancer cells. Results Numerous tumour types have elevated NDE1, which is linked to a bad prognosis. NDE1 is an excellent diagnostic tool for many different types of cancer. Numerous malignancies have been linked to genetic changes in NDE1. NDE1 was connected to TMB, MSI, several immunological checkpoint genes and immune cell infiltration. NDE1 is linked to a number of immunological subtypes. NDE1 could affect how well immunotherapy works to treat different types of cancer. NDE1 was mostly associated with cell cycle, chromosomal segregation, DNA replication and mitotic segregation, according to GO and KEGG analyses. NDE1 physically binds to PAFAH1B1 and DCTN1, respectively. The proliferation, invasion and metastasis of bladder cancer cells may be prevented by NDE1 knockdown. Furthermore, knockdown of NDE1 promoted the apoptosis of bladder cancer cells. Conclusion High expression of NDE1 is present in a variety of tumours, which is linked to a bad prognosis for cancer. Knockdown of NDE1 inhibited the proliferation, invasion and metastasis of bladder cancer cells, and promoted the apoptosis. For a number of malignancies, NDE1 may be a biomarker for immunotherapy and prognosis.